GENEOLOGI BAHASA DALAM HUMANIORA - Esha, Muhammad In’am (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2009)
This paper studies the relation between language and humanities in the history of science perspective. Based on this study there are four findings. First, relation between language and humanities in the structure of science in this modern era is not able to be divided from the background of the development of studia humanitatis in the west. Second, development of humanities in the west relates to the vision of education for presenting humanizing curriculum. This is because of the fact that the studies and research in language and classical literatures is a necessity. Third, in Islamic civilization, the term humanities is unpopular, but essentially the studies of humanities (ex: language, literature, logic, art) have strategic position. Islamic civilization is text civilization (hadlarah al-nash) based on Koran and to understand it needs the tool, mainly language science. The existence of those sciences in Islamic civilization is very significant.